International Perspectives on Critical Pedagogies in ELT - López-Gopar, Mario E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited collection brings to the forefront attempts to connect critical pedagogy and ELT (English Language Teaching) in different parts of the world. The authors in this collection write from their own experiences, giving the chapters nuanced understanding of the everyday struggles that teachers, teacher educators and researchers face within different contexts. Throughout the book, contributors connect micro-contexts (classrooms) with macro-contexts (world migration, politics and social issues) to demonstrate the impact and influences of pedagogy. In problematizing ELT and focusing on so-called 'peripheral' countries where educators have created their own critical pedagogies to respond to their own local realities, the contributors construct ELT in a way that goes beyond the typical ESL/EFL distinction. This unique edited collection will appeal to teacher educators, in-service teachers working in the field as well as students and scholars of English language teaching, second language acquisition and language education policy. Mario E. López-Gopar is Professor in the Faculty of Languages of the Universidad Autónoma Benito Juárez de Oaxaca, Mexico. His main research interests centre around the intercultural and multilingual education of Indigenous peoples in Mexico. Having received over 15 academic awards, his latest publication is Decolonizing Primary English Language Teaching (2016).
Chapter I: Introducing International Critical Pedagogies in ELT; Mario E. López-Gopar -- Section 1: Teaching Beyond Language -- Chapter II: "When I came to Canada like I heard lots of bad stuff about Aboriginal people": Disrupting Settler colonial discourses through English Language Teaching; Andrea Sterzuk and Simone Hengen -- Chapter III: Critical pedagogy in Saudi college EFL classrooms under the neoliberal economy; Osman Z. Barnawi -- Chapter IV: A Filipino L2 Classroom: Negotiating Power Relations and the Role of English in a Critical LOTE/World Language Classroom; Jayson Parba and Graham Crookes -- Chapter V: The intersections between critical pedagogy and public pedagogy: Hong Kong students and the Umbrella Movement; Christian W. Chun -- Section 2: Dialoguing With Teachers -- Chapter VI: "The Coin of Teaching English has Two Sides": Constructing Identities as Critical English Teachers in Oaxaca, Mexico; Edwin N. León Jiménez, William Sughrua, Angeles Clemente, Vilma Huerta Cordova and Alba E. Vásquez Miranda -- Chapter VII: Negotiating Gender and Sexual Diversity in English Language Teaching: "Critical"- Oriented Educational Materials Designed by Pre-Service English Teachers at a South African University; Navan N. Govender -- Chapter VIII: Teachers explore the complexity of learners' lives through ethnographic projects; Maria Dantas-Whitney -- Chapter IX: Mapping our Ways to Critical Pedagogies: Stories from Colombia; Amparo Clavijo-Olarte and Judy Sharkey -- Section 3: Questioning the Critical -- Chapter X: Educating English Language Teachers to Critical Language Awareness: A collaborative Franco-Japanese project; Christine Hélot, Masahito Yoshimura and Andrea Young -- Chapter XI: Academic Language and Learning in an Australian Context; Anne Swan -- Chapter XII: 'A Gin and Tonic and a Window Seat': Critical Pedagogy in Arabia; Paul Hudson -- Chapter XIII: Conclusion: Politicized Qualitative Research Methodology of Critical ELT Studies; William M. Sughrua.
Keywords: Applied linguistics; Germanic languages; Multilingualism; Language and languages -- Study and teaching; Language policy; Applied Linguistics; Germanic Languages; Multilingualism; Language Education; Language Teaching and Learning; Language Policy and Planning